Hybrid derivatives in contemporary Korean - Borowiak, Anna (Scripta Neophilologica Posnaniensia, 2020)
The advances in international and intercultural communication resulting in the multilingualism of native communicative communities and ultimately leading to the creation of the global communicative community, is well reflected in the lexical subsystem of many languages all around the world. This subsystem is continuously being enriched not only with numerous borrowings but also with the formations of hybrid type. As far as the Korean language is concerned, opening of the Korean borders to the world in 1876, also opened ‘the lexicon borders’ to the considerable number of Western loanwords, which, with time, started to be used in morpheme-based word-formation processes such as derivation and composition, as well as in new word-formation processes – among them blending and reanalysis. Despite the fact that there are two types of hybrid derivatives distinguished according to the origin of their counterparts (roots and affixes), which are coined and used in contemporary Korean, this article, given its scope, focuses only on the derivatives having the Koreanized bases of European provenance.